Evaluasi Efektivitas Sistem Semi Manual Dalam Penguatan Pengendalian Internal Dan Pencatatan Keuangan: Studi Kasus Pada PT Unggul Usaha Berdaya - Desinta Wulandari; Tituk Diah Widajantie (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2025)
This research aims to evaluate the effectiveness of the semi-manual accounting system in strengthening internal control and ensuring transaction accuracy during the transition from ISC ERP to SHAPE ERP at PT Unggul Usaha Berdaya. The study focuses on how hybrid systems serve as a bridge between technological change and organizational readiness, emphasizing internal control, risk mitigation, and data integrity. Using a qualitative case study method, data were obtained through interviews, observations, and documentation review. The results show that the semi-manual system enhances verification and data validation, maintains financial reliability, and functions as a preventive measure against information loss during system migration. Although it increases workload, it provides an additional control layer that strengthens accountability and audit trails. Theoretically, this research integrates the COSO internal control framework (2013) with ERP transition theory, offering new insights into hybrid control models for developing economies. Practically, it recommends structured SOP documentation, staff training, and automation readiness to ensure sustainable ERP implementation.